Analisis Humanistik Buddhisme : Tinjauan Suttra Hati - Danu Aryanto; Lery Prasetyo; Eko Siswoyo (Jurnal Budi Pekerti Agama Buddha, 2026)
This research is motivated by the importance of understanding the Heart Sutra within the framework of Humanistic Buddhism, especially for students of Buddhist religious education. The main problem lies in the limited understanding of the relevance of the Heart Sutra to humanistic values ​​in the context of modern life. This study aims to explain the relevance of the Heart Sutra teachings in building applicable spiritual, ethical, and social awareness. The method used is a literature study with a descriptive qualitative approach through text analysis and academic literature review. Data were obtained from primary sources in the form of translations of the Heart Sutra and secondary sources including journals, books, and scientific articles related to Humanistic Buddhism. The results of the study show that the teachings of sunyata (emptiness) in the Heart Sutra not only have profound philosophical meaning, but also provide practical implications in everyday life. The Heart Sutra is able to strengthen the philosophical foundation of Humanistic Buddhism, foster an attitude of compassion, wisdom, and tolerance, and serve as a relevant ethical guideline in facing the dynamics and challenges of modern society.